Sustaining Long-Run Growth and Macroeconomic Stability in Low-Income Countries : The Role of Structural Transformation and Diversification. (Policy Papers; Policy Paper ;, 2014)
Diversification and structural transformation play important roles in influencing the macroeconomic performance of low-income countries (LICs). Increases in income per capita at early stages of development are typically accompanied by a transformation in a country's production and export structure. This can include diversification into new products and trading partners as well as increases in the quality of existing products.